1999
DOI: 10.1136/jms.6.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cascade testing for fragile X syndrome

Abstract: The results of our analysis show that cascade testing is not very effective in detecting carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The estimated cost was US$45,000 per detected carrier. G Wildhagen and co-workers 110 used a microsimulation model to assess the cascade testing for FXS in The Netherlands. Cascade testing may be more efficient in terms of a better NNT (number needed to test for one detected carrier) than prenatal screening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated cost was US$45,000 per detected carrier. G Wildhagen and co-workers 110 used a microsimulation model to assess the cascade testing for FXS in The Netherlands. Cascade testing may be more efficient in terms of a better NNT (number needed to test for one detected carrier) than prenatal screening.…”
Section: Discussionmentioning
confidence: 99%
“…Wildhagen and co-workers 110 developed a microsimulation model, simulating pedigrees of five generations to obtain a population where some nuclear families were connected with others and some were not. Then the simulation data were used to estimate the efficacy of cascade testing for FXS.…”
Section: A Simulation Modelling Of Cascade Testing In the Netherlandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these identified families could benefit from genetic counseling, newborn screening is neither ideal nor designed for identifying most at-risk families for the fragile X syndrome in the general population. 120 Finally, many other issues, including educating health-care professionals and the public about the syndrome, assessing the psychological impact of carrier status, and maintaining families' privacy, should be thoroughly researched and adequately resolved before implementation of any type of routine screening for the fragile X syndrome in the general population.…”
Section: Gaps In Research Related To Screeningmentioning
confidence: 99%
“…Although FXS 16 FXS is usually diagnosed by case-finding with carriers identified through cascade testing of family members, yet the majority of carriers remain undetected. 5,17 There have been discussions regarding the feasibility, cost-effectiveness, and cost-benefit of population-based carrier screening for FXS, with arguments generally in favor. 18 -23 Others have suggested that the decision to screen should focus on medical, social, psychological, and ethical considerations.…”
mentioning
confidence: 99%